2022
DOI: 10.3390/buildings12111816
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Fire Resistance of Concrete Beams Made with Iron Tailings Sand

Abstract: In order to measure the effect of iron tailings sand replacing natural sand on the fire resistance of concrete beams, five full-scale iron tailings sand concrete (ITSC) beams and two natural sand concrete (NSC) beams were conducted to fire testing under dead load and rising temperature conditions. The section temperature field, mid-span displacement, failure form, and fire resistance limit of ITSC beams under fire were analyzed. The main influence factors included different ISTC strengths (C30 and C40) and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The increasing number of fires with a range of consequences such as death, loss of property, and financial issues has meant that fire resistance research has continually attracted the attention of scientists. As fire is the cause of the reduction in material properties and load-bearing capacity of structures [ 1 ], construction material regulations include fire resistance tests which provide an assessment of load-bearing characteristics and fire separation properties. The tests are performed in large furnaces with reference to a standard temperature–time curve [ 2 ] defined by the equation: where —time [min], and —the gas temperature in the fire compartment (°C) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The increasing number of fires with a range of consequences such as death, loss of property, and financial issues has meant that fire resistance research has continually attracted the attention of scientists. As fire is the cause of the reduction in material properties and load-bearing capacity of structures [ 1 ], construction material regulations include fire resistance tests which provide an assessment of load-bearing characteristics and fire separation properties. The tests are performed in large furnaces with reference to a standard temperature–time curve [ 2 ] defined by the equation: where —time [min], and —the gas temperature in the fire compartment (°C) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the low utilization ratio, a large amount of IOTs can only be piled up in tailing ponds, which not only encroach on the land and pollute the surrounding environment, but also require a large amount of maintenance funds [4][5][6]. To protect the environment and increase the economic benefits, the secondary use of IOTs in the construction industry has attracted the attention of many scholars [7,8]. Andrews et al [9] found that the compressive strength and splitting tensile strength of concrete were greatly improved with a 25% IOT substitution.…”
Section: Introductionmentioning
confidence: 99%